2020
DOI: 10.1002/aenm.202001826
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Electrochemical Reduction Products and Processes in Silica Anodes for Next‐Generation Lithium‐Ion Batteries

Abstract: The use of silica as a lithium‐ion battery anode material requires a pretreatment step to induce electrochemical activity. The partially reversible electrochemical reduction reaction between silica and lithium has been postulated to produce silicon, which can subsequently reversibly react with lithium, providing stable capacities higher than graphite materials. Up to now, the electrochemical reduction pathway and the nature of the products were unknown, thereby hampering the design, optimization, and wider upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…However, studies have shown that when SiO 2 is exposed to low voltages (<200 mV vs Li + /Li), it can react with Li‐ions slowly and provide a considerable specific capacity of ≈400 mAh g −1 . [ 29,30 ] The main reduction products of the SiO 2 include amorphous Si, Li 2 O and Li x Si y O z , [ 31,32 ] There into, amorphous Si and Li 2 Si 2 O 5 are electrochemically reversible; Li 2 O and other Li x Si y O z products are electrochemically irreversible, they are however mechanically stronger and more conductive than SiO 2 ; meanwhile, Li 2 O can facilitate the diffusion of Li‐ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have shown that when SiO 2 is exposed to low voltages (<200 mV vs Li + /Li), it can react with Li‐ions slowly and provide a considerable specific capacity of ≈400 mAh g −1 . [ 29,30 ] The main reduction products of the SiO 2 include amorphous Si, Li 2 O and Li x Si y O z , [ 31,32 ] There into, amorphous Si and Li 2 Si 2 O 5 are electrochemically reversible; Li 2 O and other Li x Si y O z products are electrochemically irreversible, they are however mechanically stronger and more conductive than SiO 2 ; meanwhile, Li 2 O can facilitate the diffusion of Li‐ions.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that when SiO 2 is exposed to low voltages (<200 mV vs Li + /Li), it can react with Li-ions slowly and provide a considerable specific capacity of ≈400 mAh g −1 . [29,30] The main reduction products of the SiO 2 include amorphous Si, Li 2 O and Li x Si y O z , [31,32] There into, amorphous Si and Li 2 Si 2 O 5 are electrochemically reversible; Li 2 O and other Li x Si y O z products are electrochemically irreversible, they are however mechanically stronger and more conductive than SiO 2 ; meanwhile, Li 2 O can facilitate the diffusion of Li-ions. In this work, a facile and benign one-step method is developed to synthesize multi-Si-void@SiO 2 structure in which abundant void spaces are created between multiple Si cores that are encapsulated in a SiO 2 shell. In the structure, the void spaces can accommodate the huge volume changes of Si during the lithiation/delithiation process, enhancing the structural and cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Unfortunately, the serious volume expansion of silicon (>300%) in the process of lithiation accompanied by structural fracture and pulverization limits its practical application. [25][26][27][28][29] Although massive efforts have been put in solving this issue, silicon anodes have not yet been broadly commercialized because of the costly and complex preparation. Well ahead of time, silica was considered to be electrochemically inactive toward lithium because of the low ion diffusivity and the electronic insulation.…”
mentioning
confidence: 99%
“…In contrast, the capacity is only 228 mAh g −1 after 500 cycles for the pristine Si anode, corresponding to the capacity retention of only 17.3%. As fundamental studies, low mass loadings of active materials are widely used, [ 27,34 ] for example, 0.4 mg cm −2 in the study by Ge et al, [34d] 0.5 mg cm −2 in the study by Zhang et al, [ 27 ] and 0.7 mg cm −2 in the study by Park et al [34b] Nevertheless, cycling performance at the current density of 1500 mA g −1 of Si−Sn@C/Cu 3 Si−P 260 electrode with different mass loadings is also tested (Figure S14, Supporting Information). It is seen that the apparent capacity and the cyclic stability all somewhat decreased in general when the mass loading of the active materials increased from 0.6 to 0.8 and to 1.0 mg cm −2 .…”
Section: Resultsmentioning
confidence: 99%